ИТОГИ ПОИСКА МИНУТНЫХ ФЛУКТУАЦИЙ ПОТОКА ГАЛАКТИЧЕСКИХ ИСТОЧНИКОВ МАЗЕРНОГО ИЗЛУЧЕНИЯ В ЛИНИИ ВОДЯНОГО ПАРА НА ДЛИНЕ ВОЛНЫ 1.35 СМ В 2002-2011 ГГ. - Самодуров, В. А.; Толмачев, А. М.; Вольвач, А. Е.; Сипаров, С. В.; Субаев, И. А.; Ладейщиков, Д. А.; Рудницкий, Г. М.; Вольвач, Л. Н.; Логвиненко, С. В.; Лехт, Е. Е.; Пащенко, М. И. (Одеські астрономічні публікації, 2011)
Results of a search for ultrarapid flux fluctuations of galactic sources of maser emission in the water-vapor line at a wavelength of 1.35 cm. An observational technique of a search for rapid flux fluctuations on some minute scales has been developed. From 2002 to 2011 a number of observational sessions for 49 maser sources have been carried out with durations from 2 till 7 hour (with spectra exposition from 1 second to 20 minutes). For the most interesting sources has been spent on two-three sessions with an interval a day. Among them are allocated a little which have shown such variability, among which as internal processes in the sources, going in areas the possible reasons of variability are discussed with characteristic scale of an order 0.1 a.u., and external (up to theoretical possibility of resonant influence of gravitational waves from galactic objects on area maser radiations). Fast fluctuations of spectra for 12 maser sources on scales in tens minutes and minute (for sources Cep A, GGD4, IRAS 16293-2422, Ori A, W3 (OH), W3 (2), W33B, W43M3, W44C, W49N, W75N, W75S) are found reliably out. The part from them is connected with linear polarization for some sources (Ori A, W3 (OH), W3 (2), W44C, W49N, W75S) that leads to slow changes of streams (ten minutes) from the polarized spectral details during moving of sources on the sky. Other type of variability is connected with fast movements maser condensation in space masers (Cep A, GGD4, IRAS 16293-2422, W33B, W43M3, W49N, W75N). Characteristic time of changes of fluxes of the second type of variability – from 10 minutes to about one hour.